Parametric Optimization of Kapok (Ceiba Pentandra) Oil Methyl Ester Production using Taguchi Approach - Nur, Norazahar (2012)
Utilization of new feedstock for biodiesel production has been explored. In this research, Kapok seed oil (KSO) with scientific name of Ceiba Pentandra has been used for synthesizing the biodiesel. The extraction of KSO gives about 22-25% wt/wt of oil. Pre-treatment of KSO has been done using esterification process with the presence of acid catalyst and transesterification of KOS is carried out after the pre-treatment using potassium hydroxide (KOH) as base catalyst. The biodiesel property of Kapok oil methyl ester (KOME) has been characterized and it shows that KOME meets the properties of biodiesel as stated in standard method of ASTM D6751 and EN14214.